Health Determinants: Healthy People of the UAE 2025 - 2035 Plan - Alneyadi , Rauda (Global Journal of Health Sciences, 2024)
Purpose: The goal of the Healthy People initiative is to improve the health of the nation as a whole by directing efforts that are made at the national level to promote health and prevent sickness (Healthy People, 2023). Methodology: This been a white paper the study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low-cost advantage as compared to field research. The current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found out that promoting a healthier and more informed generation requires health literacy in youngsters. The study also found out that the reduction of obesity among police officers would enhance both their general well-being and their effectiveness at work. The study indicated that a comprehensive road safety program targeting car accidents should be implemented to reduce road accidents Unique Contribution to Theory, Practice and Policy: Primary school's teachers should integrate health education as a regular part of the curriculum, The police department should establish clear and realistic goals and incentives for police officers to participate in the health and wellness programs and drivers should undergo regular training and testing to ensure they follow the traffic rules and regulations. Education authorities should support and facilitate health literacy instruction in primary schools, by providing adequate resources and training, The United Arab Emirates (UAE) government should allocate more funds and resources to support individualized health and wellness programs for police officers, as well as to raise awareness about the risks of obesity and the benefits of physical activity and healthy eating. The government should develop and implement a national road safety strategy that sets clear goals and targets for reducing car accident fatalities and injuries. This strategy should be evidence-based and regularly updated.